Determination of droop control coefficient of multi‐terminal VSC‐HVDC with system stability consideration. Issue 13 (15th March 2018) - Peng, Qiao; Liu, Tianqi; Wang, Shunliang; Qiu, Yufeng; Li, Xingyuan; Li, Baohong
Abstract : In multi‐terminal voltage source converter based high‐voltage direct‐current (VSC‐HVDC) systems, droop controllers are commonly adopted to regulate the active power and voltage. Thus, the droop controller coefficients inevitably affect the system stability. In this study, a method to design droop control coefficient is proposed considering the system stability. The state‐space model of the multi‐terminal VSC‐HVDC system with droop controllers is established in which the droop controllers are considered as feedback controllers to reflect the control characteristics. Based on the model, the determination of droop control coefficients can be equivalent to an optimisation problem. The objective is to minimise the Frobenius‐Hankel norm of the system S / T mixed sensitivity. The constraint conditions include closed‐loop system eigenvalues constraint and steady‐state errors constraint. By doing so, the optimal system stability and robustness are achieved. To verify the proposal, simulations on a four‐terminal VSC‐HVDC system are performed with two another sets of droop control coefficients for comparison. Simulation results show that the proposed droop controller can ensure system stability and robustness under various disturbances and faulty conditions.